2021
DOI: 10.1038/s41467-021-24610-x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of fragile site-associated tumor suppressor promotes antitumor immunity via macrophage polarization

Abstract: Common fragile sites (CFSs) are specific breakage-prone genomic regions and are present frequently in cancer cells. The (E2-independent) E3 ubiquitin-conjugating enzyme FATS (fragile site-associated tumor suppressor) has antitumor activity in cancer cells, but the function of FATS in immune cells is unknown. Here, we report a function of FATS in tumor development via regulation of tumor immunity. Fats−/− mice show reduced subcutaneous B16 melanoma and H7 pancreatic tumor growth compared with WT controls. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
4
15
0
Order By: Relevance
“…To further confirm if the aforementioned influence of CFT073 wt on polarization of macrophages was caused by TcpC, rTcpC was prepared and its effects on macrophage polarization were also examined. In accordance with previous reports [ 27 , 31 , 32 ], LPS + IFN-γ significantly induced the expression of M1 markers CD80 and CD86, and IL-4 treatment promoted the expression of M2 markers CD163 and CD206 in both THP-1 and J774A.1 macrophage cell lines. However, 4 μg/mL rTcpC treatment profoundly attenuated LPS + IFN-γ=induced expression of CD80 and CD86 ( Figure 4 A–D), while promoting CD163 and CD206 expression ( Figure 4 E–H).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…To further confirm if the aforementioned influence of CFT073 wt on polarization of macrophages was caused by TcpC, rTcpC was prepared and its effects on macrophage polarization were also examined. In accordance with previous reports [ 27 , 31 , 32 ], LPS + IFN-γ significantly induced the expression of M1 markers CD80 and CD86, and IL-4 treatment promoted the expression of M2 markers CD163 and CD206 in both THP-1 and J774A.1 macrophage cell lines. However, 4 μg/mL rTcpC treatment profoundly attenuated LPS + IFN-γ=induced expression of CD80 and CD86 ( Figure 4 A–D), while promoting CD163 and CD206 expression ( Figure 4 E–H).…”
Section: Resultssupporting
confidence: 93%
“…It was reported that complete polarization of macrophages to the M1 type requires activation of the MAPK and NF-κB signaling pathways [ 19 , 27 , 31 , 61 ], and M2 macrophage polarization requires activation of the STAT signaling pathway [ 62 , 63 ]. To explore the signal transduction pathways underlying the regulatory effects of TcpC on M1/M2 polarization, the influence of TcpC on MAPK/NF-κB and Akt/STAT pathways was examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). In accordance with previous reports [40][41][42] , we observed that MP depletion significantly delayed tumor growth in wildtype mice (Prkcd +/+ ) (Fig. 3B,D).…”
Section: Pkcδ Deficiency Impairs Tumor Growth and Immune Suppression ...supporting
confidence: 93%
“…Unfortunately, M1 macrophages are in the minority while M2 macrophages are in the majority of tumors. M2 macrophages are involved in tumor invasion, metastasis, and immunosuppression in various manners to promote tumor growth and development. , At present, most studies have adopted various strategies to transform the formed M2-type into M1-type macrophages, but these transformations are inefficient. Studies have revealed that the metabolic pathways of M2-type macrophages are reprogrammed in the process of maintaining their own vitality and function, such as highly dependent glutamine metabolism .…”
Section: Introductionmentioning
confidence: 99%